Implementing Islamic Marriage Rules in National Family Laws: A Case Study of Albania's Legal Framework - Nezha, Kelmend; Berdufi, Nertil; Qinami, Aranit (European Journal of Social Science Education and Research, 2023)
This paper investigates the implementation of Islamic marriage rules within the context of Albania's legal framework, focusing on the intersection between Islamic marriage practices and national family laws. It examines the issue of gender equality in marriage and divorce under Islamic law, with a particular emphasis on protecting women's rights and interests. The analysis begins by considering Islamic Law through a human rights lens, followed by a descriptive examination of Albania's Family Law as a secular state with a Muslim majority. The paper explores how Albanian Muslim couples, who enter into Islamic marriage contracts, navigate the national legal system during civil marriage registration and divorce proceedings. It aims to identify the legal challenges that may arise in such situations, considering Albanian legal regulations related to marriage and divorce. The study also delves into how family law addresses Shari'ah principles concerning marriage and divorce procedures, as well as the dynamics of gender relations in initiating divorce. Moreover, it investigates the enforcement of mahr (the husband's gift to his wife) provisions stipulated in Islamic marriage contracts and discusses how Albanian judges should respond to such requests. Ultimately, the paper explores the compatibility of enforcing Islamic marriage contracts with the law, while ensuring that their provisions do not infringe upon constitutional and human rights.
Keywords: marriage, divorce, family law, Islam, Shari'ah, contract